Extraction of Free Fatty Acid Mixtures from Rice Bran Oil by Aqueous Renewable Alcohols: Liquid-liquid Equilibrium Diagram and Number of Equilibrium Stages - I Dewa Gede Arsa Putrawan; Menur Widyasih; Rani Wulantari (Journal of Engineering and Technological Sciences, 2021)
This work is aimed to measure the liquid-liquid equilibria of rice bran oil-fatty acid-aqueous alcohols using fatty acid mixtures derived from rice bran oil as solutes and to calculate the number of equilibrium stages required for the extraction process. Renewable alcohols, ethanol and isopropanol in aqueous form were used as solvents. The liquid-liquid equilibrium data were measured at 25 °C and presented as ternary diagrams. It was found that ethanol gave a lower distribution coefficient than isopropanol. For the same solvent, increasing the water content resulted in a lower distribution coefficient. For the free fatty acid contents of 30% in the feed and of 10% to 2.5% in the raffinate, the minimum solvent-to-feed ratio was found to be in the range of 1 to 5. Using solvent-to-feed ratios from 2 to 4, the number of extraction stages required was in the range of 1 to 8. Based on the minimum solvent-to-feed ratio and number of equilibrium stages, isopropanol was found to be better than ethanol.